2001
DOI: 10.1002/ijc.1393
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms of prostate-specific antigen in serum with concentrations of total prostate-specific antigen <4 ?g/L: Are they useful tools for early detection and screening of prostate cancer?

Abstract: Molecular forms of prostate-specific antigen (PSA) improve the differentiation between benign prostatic hyperplasia (BPH) and prostate cancer (PCa) in men with total PSA concentrations between 4 and 10 g/l. To evaluate the diagnostic utility of free PSA (fPSA) and complexed PSA forms for identification of men with PCa in the low PSA range of <4 g/l, total PSA (tPSA), ␣ 1 -antichymotrypsin complexed PSA (PSA-ACT) and fPSA (Roche Elecsys [ES] system) as well as tPSA and complexed PSA (cPSA) (Bayer Immuno 1 syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
0
15
0
3
Order By: Relevance
“…Some studies demonstrated an advantage for %fPSA, 25,46 -48 and some did not demonstrate a better performance by %fPSA compared with tPSA. 49 -52 Retrospective data obtained by Jung et al 48 revealed an advantage for %fPSA compared with tPSA. In a larger group of men (n ϭ 219 patients) with tPSA in the 2-4 ng/mL range, there was no difference between tPSA and %fPSA (AUC, 0.62 vs. 0.64).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated an advantage for %fPSA, 25,46 -48 and some did not demonstrate a better performance by %fPSA compared with tPSA. 49 -52 Retrospective data obtained by Jung et al 48 revealed an advantage for %fPSA compared with tPSA. In a larger group of men (n ϭ 219 patients) with tPSA in the 2-4 ng/mL range, there was no difference between tPSA and %fPSA (AUC, 0.62 vs. 0.64).…”
Section: Discussionmentioning
confidence: 99%
“…Para sensibilidades del 90% y 95% con el PSA complejo obtienen especificidades de 25,6% y 20,1% respectivamente, mientras que con el PSA total serían de 11,1% y 9,8%. Sin embargo, Lein et al 58 y Jung et al 59 no encuentran ventajas del PSA complejo con respecto al PSA total, aunque las poblaciones estudiadas y los ensayos para medir el PSA total fueron distintos. Lein et al 58 sí que describen estas ventajas cuando analizan el cociente PSA complejo/PSA total.…”
Section: Referenciaunclassified
“…41 Studies on the use of the PSA complexes (PSA-ACT and cPSA) for low PSA values less than 4 ng/mL are rare, but these results indicate a possible use and warrant further prospective evaluations. 42,43 …”
Section: Psa-act and Cpsamentioning
confidence: 99%